Design of a Wide-Angle and Polarization-Free 1-Bit Programmable Metasurface - Liu, Lu; Huang, Yi Fei; Zhang, Hao Chi (Frontiers in Materials, 2022)
Programmable metasurfaces have powerful capability of controlling electromagnetic (EM) waves by coding the digital state of each meta-atom. However, conventional programmable metasurface units is difficult to maintain stable controllability under wide angle incidence conditions, which limits the application of 1-bit programmable metasurfaces in single-beam scanning. Here, a 1-bit dual-polarized programmable metasurface that allows oblique incidence at large angles is presented in this paper. Inspired by the principle of reciprocity in antenna theory, a wide-angle patch antenna which operating in receiving mode and loaded by a Pin-diode-based load circuit is designed as the basic structure of the meta-atom. Numerical simulations show that 1-bit coding state maintains good angular stability within ±70 degrees of incident angle for both orthogonally polarized EM waves, and single-beam scanning can be achieved at large oblique incident angles for any polarization.